A Modeling Analysis of the Apparent Linear Relation Between Mesospheric Temperatures and Meteor Height Distributions Measured by a Meteor Radar. Issue 1 (6th January 2022) - Lee, Wonseok; Lee, Changsup; Kim, Jeong‐Han; Kam, Hosik; Kim, Yong Ha
Abstract: A new method of estimating mesospheric temperature has recently been proposed by utilizing an apparent linear relation between atmospheric temperatures and full widths at half maximum (FWHMs) of meteor height distributions measured by a meteor radar (MR). However, the new method assumes that the meteor height distribution is dominantly dependent on the atmospheric conditions, rather than on meteoroid characteristics (mass and velocity). In order to verify this assumption, we have developed a meteor ablation model and applied it to the observed parameters by a MR at King Sejong Station (62.2°S, 58.8°W). The simulation results show that the FWHM of meteor height distribution increases linearly with the mesospheric temperature and its linear relation matches well with the observed relation. We found that the seasonal variation of meteor velocity distributions is significant but has only little effect on the variation of the height distribution. We also found that the observed characteristics of meteors are consistent with a Gaussian distribution of logarithmic masses, and this distribution is nearly invariable throughout the year with the average peak value of 10 − 6.2 kg ${10}^{-6.2}\hspace*{.5em}\text{kg}$ . Thus, we conclude that observed meteor height distributions are mainly dependent on the mesospheric temperature, and can be used as a mesospheric temperature indicator. Plain Language Summary: We have simulated meteor ablation to analyze the data observed by a meteor radar at an Antarctic station (King Sejong Station, 62.2°S, 58.8°W). We found that the simulated distribution of meteor heights are strongly dependent on the mesospheric temperature, rather than incoming meteor characteristics. The simulation confirms that mesospheric temperature can be estimated from the full width half maximum (FWHM) of the observed height distribution by the meteor radar, which was proposed by our previous work (C. Lee et al., 2016, https://doi.org/10.1002/2016GL071082 ). Key Points: The meteor height distribution was simulated using a meteor ablation model Simulation results show clearly the linear relationship between full widths at half maximum of the meteor height distribution and mesospheric temperatures Initial mass distributions of sporadic meteors derived from the King Sejong Station meteor radar are almost invariable over a year